Quality control of garment product using DMAIC Six Sigma - Tyas, Tiara Cahyaning; Giyanti, Ida (OPSI, 2024)
Quality control is intended to ensure that the products are in accordance with the predefined standards. PT. XYZ is a garment company that manufactures products with global target market. Hence, product quality assurance becomes an important issue for PT. XYZ. This research focuses on the Just Brand-MCJA216142 jacket product at the sewing work station on line-4 of PT. XYZ. Preliminary observations show that the number of reworked-products was experiencing an increasing trend. This study aims to determine whether the company has carried out quality control properly. Specifically, the research objectives are to identify the type and level of product defects, identify the factors causing product defects, and provide proper improvement suggestions to reduce the occurrence of product defects. This study applied DMAIC (Define–Measure–Analyze–Improve–Control) Six Sigma concept. The results showed that the quality of the Just Brand-MCJA216142 jacket product has exceeded the Indonesian industry average and is classified as the USA industry average. However, quality improvement is still needed since the products are targeted for the export market. Based on Pareto diagram at the Analyze stage, it was found that the most dominant defects occurred in the Just Brand-MCJA216142 jacket production process were broken threads and puckering. The frequency of occurrence for these two types of defect reaches 23% of the total 16 types of defects. The defects were caused by human, machine, material, method, and environmental factors. Recommendations for improvement at the Improve stage are based on root cause analysis of each causative factor that is identified using a fishbone diagram. This research results strengthen the previous related researches regarding the effectivity of DMAIC Six Sigma for analyzing quality control of products.